IBM DS8900F product guide release 9.3 - Cook, Jeff; Kimmel, Peter; Riggins, Connie (IBM Redbooks, 2022)
This IBM® Redbooks Product Guide provides an overview of the features and functions that are available with the IBM DS8900F models that run microcode Release 9.3 (Bundle 89.30/Licensed Machine Code 7.9.30).